Ethnolinguistic Identification, Vitality, and Gratifications for Television Use in a Bilingual Media Environment. (March 2015) - Harwood, Jake; Vincze, Laszlo; Mastro, Dana; Tukachinsky, Riva
<x xml:space="preserve">Abstract</x> This article tests a model predicting minority language television consumption. We examine how four media gratifications (diversion, ethnolinguistic identity, surveillance, parasocial companionship) mediate the relationship between ethnolinguistic identification and choice of ingroup language television viewing. The study is performed among (minority) Hungarian speakers in Transylvania, Romania. Self‐report questionnaire data from 401 Hungarian‐speaking high school students in Csíkszereda/Miercurea Ciuc (a majority Hungarian locale) and Brassó/Brașov (a minority Hungarian locale) allowed us to compare high and low local vitality conditions. Analysis indicates that diversion (entertainment) and ethnolinguistic identity gratifications for watching ingroup language television are the strongest mediators of the influence of identification on ingroup language television use. We examined four moderators of these indirect effects (objective vitality, subjective vitality, intergroup contact, and intragroup contact). The moderators revealed a number of rather complex effects which are discussed with regard to the local intergroup context and broader issues of media and intergroup relations.